(untitled) (Publicaciones en Ciencias y Tecnología, 2022)
Motivated by the global pandemic caused by Covid-19 during the years 2020 and 2021, scientific research and its dissemination in international journals were affected by the impact of this disease. This editorial reflects on the effects during those years considering some figures on published documents and journals indexed worldwide, in Latin America and in Venezuela, published in recognized scientific databases. The editorial work of scientific journals does not stop, even during the pandemic, and in the case of Venezuelan journals, although they were affected, they continue to fulfill their mission of scientific dissemination, especially through open access platforms.